Literasi Digital, Pemanfaatan Media Pembelajaran dan Kemandirian Belajar: Kontribusinya terhadap Prestasi Akademik di SMA Intensif Taruna Pembangunan Surabaya - Rizal, Mas Ishaq; El-Yunusi, Muhammad Yusron Maulana; Darmawan, Didit (EduInovasi: Journal of Basic Educational Studies, 2024)
Education in the digital era requires the development of learning methods that are innovative and responsive to technological advances. Digital literacy and the use of learning media have an important role in improving student learning achievement. The aim of this research is to determine the impact of digital literacy and the use of learning media on student learning achievement at Taruna Pembangunan Intensive High School Surabaya. Digital literacy is considered the key to opening students' access to digital learning resources, improving understanding and providing a competitive advantage. The use of learning media with various approaches is also considered to have a positive impact on student learning achievement. Using quantitative methods, data was collected from 148 class XI students via questionnaire. Regression analysis is used to evaluate the relationship between variables. The research results show that the two independent variables have a significant influence on student learning achievement. Therefore, it is recommended to increase digital literacy and utilize learning media in curriculum planning and learning strategies.